O CONCEITO DE SUSTENTABILIDADE COMO ESTRATÉGIA DE MARKETING NA AVALIAÇÃO DA RENTABILIDADE DE FUNDOS DE INVESTIMENTO NO MERCADO BRASILEIRO - Pinheiro, Marcus André Cortez (2013)
This research aims to identify the importance of applying the concept of The Triple Bottom Line in the investment funds management by analysing the investors behavior concerning buying and selling. Therefore, this paper analyses the topic of sustainability by the investment funds trade point of view, verifying if the ones which adopt sustainable practices get competitive advantages and distinguish themselves from the others in the market. It also verifies the investment funds contribution to spread the concepts of sustainability. Owing to this context, it is unavoidable the comparison between the investment funds which adopt the sustainable practices and those that don t. After getting data (reports, researches and documents) from official institutions, the Brazilian Financial and Capital Markets Association and enterprises, this paper intends to relate the features and concepts of sustainability with the brazilian investment funds industry. It was used also academic articles, publications, magazines and sites with contents related to the issue, concerning the national investment funds market after the implementation of Real Plan, considering the period of 2007 until 2011.